Crystal structure of 2-chloro-1,3-(2,6-diisopropylphenyl)-4,5-dihydro-1H-imidazol-3-ium tetrakis(3,5-trifluoromethylphenyl)borate - Stack, Darcie L. (Acta Crystallogr E Crystallogr Commun, 2016)
The title compound, C(27)H(38)ClN(2) (+)·C(32)H(12)BF(24) (−), was synthesized by reacting the product formed from a previous reaction between 1,3-bis(2,6-diisopropylphenyl)imidazolinium-2-carboxylate (SIPrCO(2)), and SOCl(2), with sodium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (NaBARF). In the cation, the imidazole ring is in a half-chair conformation and the formerly carbene carbon atom is bonded in a distorted trigonal–planar geometry with N—C—Cl angles of 122.96 (16) and 122.21 (16)° and an N—C—N angle of 114.83 (18)°. In the crystal, weak C—H⋯F hydrogen bonds link the cations and anions, forming a three-dimensional network. In addition, a short Cl⋯F contact of 3.213 Å and several short F⋯F contacts less than the sum of the van der Waals radii [1.47 Å + 1.47 Å = 2.94 Å] are observed. The F atoms of two of the CF(3) groups were refined as disordered over four sets of sites.